PEMANFAATAN BAP DENGAN VARIASI KONSENTRASI DAN LAMA PERENDAMAN UNTUK MERANGSANG PERTUMBUHAN TUNAS BULBIL PORANG (Amorphophallus muelleri Blume) - Hera, Novita; Desrita, Nofia; Taslapratama, Irwan (Jurnal Agroteknologi, 2025)
Porang (Amorphophallus muelleri Blume) is an agricultural commodity with increasing export value; however, its production is limited by challenges in propagation. Bulbil propagation is considered the most effective method, but it is hindered by a dormancy period that prolongs the growth process. One potential solution is the application of cytokinin-type plant growth regulators, such as Benzyl Amino Purine (BAP). This study aimed to determine the optimal combination of BAP concentration and soaking duration to stimulate shoot growth in porang bulbils. The experiment was conducted from September to November 2023 at the Agronomy and Agrostology Laboratory and the UIN Agriculture Research and Development Station (UARDS) screen house, Faculty of Agriculture and Animal Science, Universitas Islam Sulthan Syarif Kasim Riau. A Completely Randomized Design (CRD) with two factors was used: BAP concentration (0, 50, 100, and 150 mg/L) and soaking duration (1, 2, and 3 hours), with three replications. Observed parameters included germination capacity, time to shoot emergence, shoot length, number of shoots, and percentage of rooted shoots. Results showed that the combination of 150 mg/L BAP and 3 hours of soaking produced the best outcomes in terms of germination capacity (100%), time to shoot emergence (21 days), shoot length (34.2 cm), and number of shoots (205). The highest percentage of rooted shoots (59.1%) was observed with a BAP concentration of 50 mg/L, while the best soaking time for rooting (56.7%) was 1 hour. In conclusion, the most effective treatment for promoting porang bulbil sprouting was 150 mg/L BAP with a soaking duration of 3 hours.